Virtue-book: Digital fairytale book for the teaching of integrity and learning recovery after the covid-19 pandemic - Hermanto Hermanto; Nanda Veruna Enun Kharisma (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2023)
Integrity and learning loss are two problems in Indonesian education due to the Covid-19 pandemic. After schools reopen in the post-pandemic period, improving integrity and learning recovery are two priorities. This study aims to develop VIRTUE-BOOK as a learning media to increase integrity and decrease learning loss for learning recovery for 3rd-grade elementary school students. This research used research and development (R&D) with the ADDIE model. There were two experts, three teachers, and 32 students as the subjects. A purposive sampling technique established the subjects. The data collection technique used scales andÂ questionnaires. The data analysis used descriptive statistics. The results show that: 1) at the design stage, the preliminary product of VIRTUE-BOOK has been produced; 2) at the end of the development stage, several assessments were carried out through expert validation scales, and they were found that the VIRTUE-BOOK is very feasible for teaching 3rd-graders about integrity and moral value of a fairytale; while the practicality response questionnaires of teachers and students show that VIRTUE-BOOK is very practical to use.